The Effect of Hypertension Self-Medication Socialization and the Relationship of Sex with Hypertension Groups in the Community of RT 04, RW 05 Cawang, East Jakarta - Kartika Rahma; Nabilah Istiyani; Tesha Sari Angrainy Rodesia; Frida Octavia Purnomo (Universitas Binawan, 2022)
Hypertension is a threat to public health because of its potential to cause complications. Providing education about hypertension in the form of prevention and treatment which is one of the treatments, so that it can change people's behavior towards their daily lifestyle. This research was conducted by 20 respondents. In activities that involve all communities in the area of RT 04, RW 05, Cawang Village, the aim is to provide health facilities to the community and provide information on how to use drugs properly and correctly, especially for hypertension drugs and find out the relationship between sex and hypertension. The results showed that there was have significant relationship between gender and hypertension group as indicated by the results of the chi-square test P-value 0,01 < α = 0.05